On the Resurrection of Trans-Temporal Inhibition - Tart, Charles (Journal of Scientific Exploration, 2017)
Application of basic learning theory to multiple choice ESP tests, like card guessing with delayed feedback, characterized this standard procedure as an extinction paradigm, an analysis supported by the empirical finding in the literature of frequent declines in ESP performance with continuing practice. The theory predicted the elimination of declines and possibilities of learning improved performance with immediate feedback in percipients who possessed some demonstrable ESP ability to begin with. In a 3-stage Selection, Confirmation (for ESP ability) and Training Study, not only were declines absent, but much higher ESP hitting than usually seen on the present time target was observed. A later exploratory analysis showed unexpected and very strong ESP missing on the immediately future target. The theory postulated to explain this, Trans-Temporal Inhibition (TTI), parallels sensory enhancement processes in our ordinary senses, and, perhaps more importantly, suggests that some aspect of the mind may have a temporally wider “now” than our ordinary “now.” The author hopes that presentation and discussion of this material here may stimulate others to devise more adequate physical theories about the nature of time and/or psychological theories about information processing procedures in ESP.